Scotland's Second War of Independence, 1332-1357 - MacInnes, Iain A. (Warfare in history., 2016)
"The Second Scottish War of Independence began in 1332, only four years after the previous conflict had ended. Fought once more for the continued freedom of Scotland from English conquest, the war also witnessed a revival of Scottish civil conflict as the Bruce-Balliol fight for the Scottish crown recommenced once more. Breaking out sporadically until peace was agreed in 1357, the Second Scottish War is a conflict that resides still in the shadow of that which preceded it: compared to the wars of William Wallace and Robert Bruce, Edward I and Edward II, this second phase of Anglo-Scottish warfare is neither well-known nor well-understood. This book sets out to examine in detail the military campaigns of this period, to uncover the histories of those who fought in the war, and to analyse the behaviour of combatants from both sides during ongoing periods of both civil war and Anglo-Scottish conflict. It analyses contemporary records and literary evidence in order to reconstruct the history of this conflict and reconsiders current debates regarding: the capabilities of the Scottish military; the nature of contemporary combat; the ambitions and abilities of fourteenth-century military leaders; and the place of chivalry on the medieval battlefield."